OPTIMALISASI PEMERINTAH DAERAH NAGAN RAYA DALAM MEMBERIKAN PEMAHAMAN KEPADA APARATUR GAMPONG MENGENAI UNDANG-UNDANG DESA - Nellis Mardhiah (Jurnal Public Policy, 2016)
The implementation of the law number 6 in 2014 to develop the potential of the Village. Robbins Relations Theory Approach may reflect the existence of laws that observed the social behavior of the readiness of local governments either internally or externally in the construction of village officials to develop a sustainable village development. The approach used survey research, the research subjects were the deepest areas of the districts are Tadu Raya, with in-depth interviews. The results showed that the government district of Nagan Raya district election Tadu Raya internally was ready to carry out training activities Gampong government management of the planning activities in preparation of the role and functions of the Village Community Empowerment Board (LPMG) suitable RPJMG and RKPG or APBG. But in terms of the implementation of the program at the village level is still weak education resources in the management of village officials in the Village. Understanding of the continuity in the government district of Nagan Raya has been optimized to BAPPEDA coordinate and implementation BPM for construction to government village in the entire region Nagan Raya district. Conclusion The district government has worked well, but on the other side of the empowerment of village officials in improving education and training need assistance and guidance on a regular basis from the local government level in order to achieve self-reliance in the success of sustainable development. And can optimize the ongoing duties and functions as LPMG regulations.Keywords: Optimization, Understanding, Administrative Village, Public Policy